2019
DOI: 10.1159/000502824
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on Human Papillomavirus Type Distribution among Women with Cervical Neoplasia in the WHO Eastern Mediterranean Region

Abstract: <b><i>Introduction:</i></b> To date, the human papillomavirus (HPV) vaccine has not been integrated into the national vaccination program of most countries of the WHO Eastern Mediterranean Region (EMRO), except for the United Arab Emirates and Libya. The knowledge of HPV genotype distribution in cervical neoplasia is valuable to predict the impact of current HPV vaccines on cancer prevention and can help the health policymakers to select the most appropriate vaccine types in their count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 74 publications
6
10
1
Order By: Relevance
“…HPV genotyping indicated that CINs were mainly positive for HPV16, followed by HPV18. Our data are in agreement with previous investigations indicating that HPV16 was the most common genotype in uterine cervical precancerous lesions, followed by HPV 18 (Shoja et al, 2019). However, other studies reported additional HPVs, including HPV 6/11/31/33/45, although at lower prevalence (Ogembo et al, 2015;Shoja et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…HPV genotyping indicated that CINs were mainly positive for HPV16, followed by HPV18. Our data are in agreement with previous investigations indicating that HPV16 was the most common genotype in uterine cervical precancerous lesions, followed by HPV 18 (Shoja et al, 2019). However, other studies reported additional HPVs, including HPV 6/11/31/33/45, although at lower prevalence (Ogembo et al, 2015;Shoja et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…The most prevalent HPV in this study was genotype 16 at 42.9%, which is in line with the findings of most studies conducted in the region (28,31,33,34), and other areas of the world where the HPV vaccine was not implemented effectively (32,35). Other results in this study might deviate from the findings reported elsewhere due to a difference in the age group compared to other studies.…”
Section: Discussionsupporting
confidence: 87%
“…The infection rate during these ages was significantly higher compared to other age groups, suggesting a “U”-shaped infection. Our results are not in agreement with previously studies where authors reported that the highest peak was obtained for younger women (under 25 years old), then a decreasing trend with age was observed and another maximum peak around 50 years old [ 15 , 19 23 ]. Many variables including geographic locations and population, demographic factors and possibly vaccination could be responsible for this difference in the prevalence of HPV-positive status and age trend modification.…”
Section: Discussioncontrasting
confidence: 99%
“…We can conclude that despite the small size of our subgroup, our results are in agreement with several reports. Our data confirm the correlation between HPV infection prevalence and the gravity of cervical intraepithelial neoplasia subgroup [ 23 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 89%